2014
DOI: 10.21149/spm.v56i3.7342
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic status and misperception of body mass index among Mexican adults

Abstract: Objective. To estimate the association between perceived body mass index (BMI) and socioeconomic variables in adults in Mexico. Materials and methods. We studied 32 052 adults from the Mexican National Health and Nutrition Sur­vey of 2006. We estimated BMI misperception by comparing the respondent’s weight perception (as categories of BMI) with the corresponding category according to measured weight and height. Misperception was defined as respondent’s perception of a BMI category different from their actual c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 25 publications
(26 reference statements)
2
14
0
1
Order By: Relevance
“…It has been argued that identification leads to a more accurate self-perception of BMI, in the case of the obese [17, 29]. However, it has also been shown that over-assessment of weight is prevalent [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been argued that identification leads to a more accurate self-perception of BMI, in the case of the obese [17, 29]. However, it has also been shown that over-assessment of weight is prevalent [13].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies also exist for the Mexican population with differing points of emphasis. Adult-based investigations are mainly divided into separate male and female studies that then include other conditions, including socioeconomic status [17] and age [18, 19]. Several studies have compared similar groups between Mexico and the United States [2022].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inaccurate perception of one's own body weight is a relatively common phenomenon observed in adolescents and adults [1][2][3][4][5][6][7][8]. It has been suggested that body weight misclassification may begin from adolescence and continue to adulthood [9][10][11], and that body weight misclassification may enhance vulnerability to some physical and mental health problems including increase in body weight, following unhealthy diet, anxiety, and depression [1,[12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Comparing studies of adolescent and adult weight misclassification, it is unclear whether misclassification is more or less common among adults than among adolescents, particularly for people who are overweight or obese [1,2,[4][5][6][7]. Several studies have reported that body weight misclassification among overweight and obese adults ranges from 37% to 62%, whereas others show that from 44.7% to 80.9% overweight and obese adolescents misclassified their body weight [1,5,8,20]. The magnitude of weight misclassification prevalence might vary depending on the methods used to measure weight perception (e.g., word or verbal descriptions, sketch, or figures).…”
Section: Introductionmentioning
confidence: 99%